1988
DOI: 10.1159/000469158
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Plasminogen Activators to Neoplastic Growth

Abstract: The topics reviewed in this article include transcriptional regulation of plasminogen activators, their relevance to differentiation, tumor progression, and to the metastatic spread of cancer. Recent information on the nature of cellular plasminogen activator receptors is also discussed. Particular attention is paid to the increasing number of observations indicating that several of the inducers of plasminogen activator synthesis utilize distinct regulatory pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 45 publications
0
29
0
2
Order By: Relevance
“…Elevated levels of proteases are present in solid tumors of the breast, ovary, colon, stomach, prostate and lung [1][2][3][4][5][6][7][8]. Collagenases, cathepsins, plasmin and plasminogen activators are found at various locations; in the cytoplasma, on the cell surface or released into the extracellular space [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of proteases are present in solid tumors of the breast, ovary, colon, stomach, prostate and lung [1][2][3][4][5][6][7][8]. Collagenases, cathepsins, plasmin and plasminogen activators are found at various locations; in the cytoplasma, on the cell surface or released into the extracellular space [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…protease activity, growth factors, steroid hormones, immunogenicity, cell adhesion, attachmeat factors). Elevated levels of the cysteine proteases, cathepsin B, L and uPA, have been correlated with increased malignancy [3,4,5,8,[17][18][19][20][21][22]. This may be due to the fact that cysteine proteases efficiently convert soluble or tumor cell receptor-bound pro-uPA to catalytically active two-chain HMW-uPA [16].…”
Section: Introductionmentioning
confidence: 99%
“…The remodelling it involves requires the coordinated action of cell-secreted proteolytic enzymes and their inhibitors. Elevated levels of urokinase-type plasminogen activator (uPA) have been implicated in these invasive processes (Dano et al, 1985;Duffy, 1987;Layer et al, 1987;Markus et al, 1988;Pyke et al, 1991b), and plasminogen activator inhibitor type 1 (PAI-1) has been found in many types of malignant tissue (Kruithof et al, 1988;Cubellis et al, 1990;Foucre et al, 1991;Tanaka et al, 1991;Reilly et al, 1992). Plasminogen activator inhibitor type 2 (PAI-2) is one of the primary physiological inhibitors of uPA.…”
mentioning
confidence: 99%
“…Stimulation of human peripheral blood granulocytes by N·formyl chemotactic peptide CHO·NLPNTL Granulocytes were isolated essentially as described.13) Briefly, 50 ml of fresh human blood obtained from four healthy donors was anticoagulated with 5,000 units of heparin and immediately centrifuged througb Ficoll-Hypaque. The cell pellet was resuspended and residual erythrocytes were lysed by using 0.16 M NH 4 Cl containing 12 mM NaHCO J , 0.1 mM EDTA, pH 7.3. Granulocytes were washed with PBS.…”
Section: Methodsmentioning
confidence: 99%